Knowledge level of sports injury first aid using PRICE method among student-athletes in Indonesia: A case study - Hison Naji Ar Rahman (Sport, Exercise, and Injury, 2025)
Background: Sports injuries are a risk often experienced by athletes, including special sports class students, so knowledge about proper injury management is needed, one of which is the PRICE method (Protection, Rest, Ice, Compression, Elevation). Objectives: This study aimed to assess the level of knowledge about first aid in sports injuries using the PRICE method among student-athletes. Methods: This study used a descriptive quantitative method with a survey technique. The research sample comprised 18 students selected through purposive sampling, using an instrument in the form of a questionnaire containing 48 items related to the PRICE method. Results: The results showed 33.3% of students had a high level of knowledge, 38.4% were moderate, 22.3% were low, and 5.5% were very low. Conclusions: The level of student knowledge of the PRICE method is mainly in the moderate to high category, but there are still some students with low understanding, especially in the Compression aspect, so further education is needed to improve the effectiveness of injury management. The compression component had the lowest understanding, indicating a need for further education and training.